(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
The article focuses on the preparation and physicochemical properties of dyes for dyeing composite fibers, provides a number of comments and examples, and describes its role in a number of studies. In addition, the physicochemical properties of mixed fibers were studied.